Densification of high-strength B4C–TiB2 composites fabricated by pulsed electric current sintering of TiC–B mixture. (1st July 2017) - Liu, Zetan; Wang, Dewen; Li, Jiamao; Huang, Qing; Ran, Songlin
Abstract: The densification and mechanical properties of B4 C–TiB2 composites fabricated by reactive pulsed electric current sintering from a mixture of TiC and amorphous B powders were investigated. The excess of B was essential to remove the carbon produced by the reaction. The degassing process at 1900 °C before applying a 50 MPa external pressure greatly improved the densification of the composites. The B4 C–41 vol% TiB2 composite obtained at the optimum condition had a high 3-point bending strength of 891 MPa, a Vickers hardness of 28 GPa and a fracture toughness of 4.4 MPa m 1/2, respectively. Graphical abstract: